Improving the effectiveness of senior graders’ education based on the development of mathematical intuition and logic: Kazakhstan’s experience - Popova, Yuliya; Abdualiyeva, Marzhan; Torebek, Yerlan; Yelshibekov, Nurgali; Omashova, Gaukhar (Frontiers in Education, 2022)
Mathematical learning in many developing nations is below average due to which students face difficulties in solving the equations and problems of mathematics as a result of limited understanding of the main concepts and reliance upon intuition as well as memorization. This study is focused on analyzing the effectiveness of senior graders’ education based on the development of mathematical intuition and logic in the context of Kazakhstan’s educational system. The quantitative research method and primary data sources were used for this research with a 147 sample size, which was selected by using a random strategy of sampling. With the use of IBM SPSS STATISTICS for data analysis, it was concluded that mathematical intuition and logic have a positive influence on the effectiveness of a student’s education. Effective strategies, such as rote learning instructions, problem-based learning, RME approach, mathematical reasoning, etc., are essential for enhancing the capabilities of studies in learning mathematics. It is found that there is a significant and positive association between student effectiveness and the logical reasoning abilities of students. Additionally, a positive and moderate relationship is noticed between the critical thinking of students, problem-solving abilities of students, and student effectiveness. Nevertheless, the main limitation of this study is that with small sample size, the findings of the study cannot be generalized; therefore, a large sample size would increase the reliability of the results in the future research. However, in the context of Kazakhstan, this study potentially contributes to the existing literature by presenting conclusive findings in the context of mathematical logic and intuition and student effectiveness.